Income and extratropical cyclones in New Zealand. (1st June 2022) - Roy, Apurba; Noy, Ilan; Cuffe, Harold E.
Abstract: Aotearoa New Zealand is highly vulnerable to extratropical cyclones because of its unique location in the midlatitude south pacific region. This study empirically investigates the impact of the extratropical cyclones on individual income, combining the data from Statistics New Zealand's Integrated Data Infrastructure (IDI) and the weather-related insurance claims data from the Earthquake Commission. Our sample covers the administrative longitudinal panel data of all the IRD registered individual taxpayers between 2010 and 2019. We estimate a set of panel regressions with individual and time-fixed effects to assess the impact of extratropical cyclones on the affected individual's annual income. We find that income from salaries and wages is negatively affected by the cyclones across various specifications. Extratropical cyclones also negatively affect the total individual income from wages and salaries, benefit and compensation, and sole tradership. However, we have limited success in identifying individual characteristics influencing the affected people's income level in our study. Highlights: Aotearoa New Zealand is highly vulnerable to extratropical cyclones. Individual income from salaries and wages is negatively affected by extratropical cyclones. Extratropical cyclones' impact on income earned by males is higher than on female income.